Vacuum-assisted vaginal deliveries among parturients with congenital uterine anomalies; risk factors and outcomes. (October 2021) - Rotem, Reut; Barg, Moshe; Sela, Hen Y.; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav
Highlights: Data regarding instrumental deliveries in those with malformed uterus is scares. In this study, maternal and neonatal outcomes in this population were examined. Instrumental vaginal deliveries were associated with unfavorable maternal outcomes. Aside from birth trauma, neonatal results did not differ between the groups. These findings should be presented during consultations about modes of delivery. Abstract: Objective: To evaluate the maternal and neonatal outcomes associated with vacuum-assisted vaginal delivery (VAVD) in a subset of parturients with congenital uterine anomalies. Study Design: A retrospective database study was conducted at a single tertiary center between 2005 and 2019. Parturients with known congenital uterine anomalies who had vaginal deliveries were enrolled, whereas parturients with failed VAVD, didelphic uterus, and delivery after intrauterine fetal death were excluded. Various maternal and neonatal outcomes were compared between parturients who achieved spontaneous vaginal delivery (SVD) and those who delivered via VAVD. The maternal composite outcome was calculated for each group and included one or more of the following: post-partum hemorrhage, hemoglobin drop ≥ 4 gr/dL, blood transfusions, retained placental products, and obstetric anal sphincter injuries. Univariate analysis was performed followed by multivariate logistic regression analysis controlling for potential confounders. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated. Results: After the application of the exclusion criteria, 332 parturients were found eligible. Of those, 289 (87%) had SVD and 43 (13%) had VAVD. VAVD was more common among primiparous parturients and epidural analgesia users. Parturients with VAVD had higher rates of third-degree perineal tear, postpartum hemorrhage, and blood transfusions. The maternal composite outcome was significantly more prevalent in the VAVD group (44.2% vs. 20.8%, p < 0.01). After controlling for potential confounders, the maternal composite outcome was found to be independently associated with VAVD (aOR 2.3, 95% CI 1.10–4.60). The neonatal results were overall comparable, except for scalp trauma and Erb's palsy/clavicular fracture, which were more prevalent in the VAVD group. Conclusion: In a special population of parturients with congenital uterine anomalies, VAVD was found to be associated with significantly higher rates of adverse maternal outcomes and perinatal birth trauma. These findings should be presented to parturients during consultations about modes of delivery.